Association of the CBLB gene with multiple sclerosis: new evidence from a replication study in an Italian population. Issue 3 (30th October 2010) - Corrado, Lucia; Bergamaschi, Laura; Barizzone, Nadia; Fasano, Maria Edvige; Guerini, Franca R; Salvetti, Marco; Galimberti, Daniela; Benedetti, Maria Donata; Leone, Maurizio; D'Alfonso, Sandra
Abstract : Background: The T allele of rs9657904 within the CBLB gene was recently found to be significantly associated with multiple sclerosis (MS) in a genome-wide association study in Sardinia. Objective: To replicate this association in an independent population with a different genetic background. Methods: The rs9657904 variant was typed in a sample of 1435 cases and 1466 controls from the Italian mainland. Results: It was found that in this sample also, the common allele T of rs9657904 is significantly positively associated (one-tailed p=7.35×10 -5 ) and with a comparable effect size with MS (OR=1.31, 95% CI 1.14 to 1.52). Conclusion: These data provide further evidence of the association of MS disease with variation within CBLB.